RETRACTED: Evolving network systems through blockchain innovation for smart agriculture IoT networks - Nuriev Marat; Aygumov Timur; Zaripova Rimma; Nikolaeva Svetlana; Gumerova Guzel (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001